Multinationals and Anti-Sweatshop Activism - Harrison, Ann; Scorse, Jason (American Economic Review, 2010)
During the 1990s, anti-sweatshop activists campaigned to improve conditions for workers in developing countries. This paper analyzes the impact of anti-sweatshop campaigns in Indonesia on wages and employment. Identification is based on comparing the wage growth of workers in foreign-owned and exporting firms in targeted regions or sectors before and after the initiation of anti-sweatshop campaigns. We find the campaigns led to large real wage increases for targeted enterprises. There were some costs in terms of reduced investment, falling profits, and increased probability of closure for smaller plants, but we fail to find significant effects on employment. (JEL F23, J31, J81, L67, O14, O15)